Development and Performance Evaluation of a Manually Operated Groundnut Roaster - Unguwanrimi, Y. A.; Okaiyeto, S. A.; Sada, A. M.; Ogijo, S. I.; Jonga, J. B.; Oji, N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
A manually operated groundnut roaster was developed and evaluated. The present Institute for Agricultural Research, Zaria (IAR) roasting equipment consists of a frying pan and an IAR charcoal fire wood cooking stove. The roaster was designed to help local processors obtain uniformly roasted products, with acceptable roast color. The performance of the roaster was carried out using IAR groundnut species known as SAMNUT 11 as specimen. The roaster was found to have a roasting capacity of 0.92 kg/min which is above the (IAR) roaster that has a roasting capacity of 0.28 kg/min. The roaster was found to have efficiencies of 98.3%, 98.6%, and 98.9% at 25%, 50% 100% loadings, respectively. The parameters that affect the roasting capacity include: heat from charcoal, crop moisture content and crop variety.